In Vitro Production and Infectivity of Oncobasidium Theobromae Talbot and Keane Basidiospores - Vadamalai, Ganesan (1999)
In vitro sporulation of Oncobasidium theobromae Talbot & Keane was induced using a modified version of the system by Shari Fudin (1995) by exposing 14 day old cultures to saturated moist air from a humidifier. Basidiospore production was able to be repeated consistently using the new system where a black perspex cabinet was used as an enclosure but the number of spores produced was low (not exceeding 36,300 spores per ml). Sporulation occurred when cultures were exposed to a mean relative humidity above 90% and low mean temperature (< 26°C). Duration of exposure to saturated moist air was vital for in vitro sporulation. O. theobromae cultures produced spores when exposed to continuous saturated moist air for more than 240 mins/day but significantly higher counts and faster formation of spores were achieved at exposures of 480 mins/day to saturated moist air. 14 days old cultures gave high spore counts. Observations indicated that the presence of monilioid hyphae was necessary for sporulation of O. theobromae since the basidium arises from it, but the formation did not appear to be influenced by factors of sporulation like saturated moist air. There was no significant difference in the formation of monilioid hyphae when the duration of exposure of cultures to saturated moist air was varied. Basidia only formed when the cultures were exposed to more than 240 mins/day of saturated moist air but the duration of exposure to saturated moist air did not appear to influence the quantity of basidia formed in cultures. Sporulation was improved by maintaining the modified system under controlled environmental conditions with the temperatures between 21°C-23°C and the mean relative humidity above 90%. Cultures were exposed to continuous saturated moist air for 480 mins/day. The spore production under these conditions was consistent with mean spore counts ranging from 62,300 spores/ml to 120,000 spores/ml. The spores produced were viable as confirmed by an average spore germination of 46% and 57.5% after 12 hours and 24 hours incubation in the laboratory